Model-Based Development of Autopilot for a Gasodynamically Controlled High-Speed Unmanned Aerial Vehicle - Jacewicz, Mariusz; Miedziński, Dariusz; Chmaj, Grzegorz; Głębocki, Robert (Journal of Automation, Mobile Robotics and Intelligent Systems, 2025)
In recent years, model-based design and automatic code generation have gained popularity in various applications. However, using this approach in some specialized safety-critical applications is still challenging because the code must fulfill rigorous requirements. In this paper, the methodology of development of the software autopilot for the surface-to-surface guided projectile is presented in detail. The missile is actuated only with 32 solid propellant lateral motors, which makes the control task challenging. MATLAB and Simulink were used to develop the detailed simulation of the missile together with the control software. A Model-in-the-Loop testing was evaluated to achieve appropriate autopilot performance. Embedded Coder was applied to generate production-ready C code from the model. A custom test framework was created to accelerate the design process. The numerical equivalency of the Simulink model and C code was investigated extensively using Software-in-the-Loop and Processor-in-the-Loop simulations. The developed control algorithm was implemented on real hardware with ARM Cortex M4 microcontroller. The integrated prototype of the projectile control system was successfully tested in laboratory conditions by Hardware-in-the-Loop simulation. The scientific significance of this paper lies in a comprehensive description of the methodology that might be used in the external ballistics area.